2016
DOI: 10.1136/gutjnl-2015-310162
|View full text |Cite
|
Sign up to set email alerts
|

Low progression of intraductal papillary mucinous neoplasms with worrisome features and high-risk stigmata undergoing non-operative management: a mid-term follow-up analysis

Abstract: In elderly patients with IPMNs that have worrisome features, the 5-year DSS is 96%, suggesting that conservative management is appropriate. By contrast, presence of high-risk stigmata is associated with a 40% risk of IPMN-related death, reinforcing that surgical resection should be offered to fit patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
122
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(133 citation statements)
references
References 32 publications
8
122
2
1
Order By: Relevance
“…Whereas the development of WF during this period is concerning, 80% of them are accounted for by cysts growing to greater than 3 cm in size which does not automatically portend malignancy or a worse outcome. In fact one study of untreated presumed BDIPMN with WF showed a 5 year disease specifi c survival of 96% ( 22 ). However, what is concerning from this paper is the late development of HRS, which accounted for two of the three patients who developed malignancy in this study.…”
Section: Pancreas and Biliary Tractcontrasting
confidence: 46%
See 2 more Smart Citations
“…Whereas the development of WF during this period is concerning, 80% of them are accounted for by cysts growing to greater than 3 cm in size which does not automatically portend malignancy or a worse outcome. In fact one study of untreated presumed BDIPMN with WF showed a 5 year disease specifi c survival of 96% ( 22 ). However, what is concerning from this paper is the late development of HRS, which accounted for two of the three patients who developed malignancy in this study.…”
Section: Pancreas and Biliary Tractcontrasting
confidence: 46%
“…One large cohort of presumed BD-IPMN patients followed for longer than 5 years had a 0, 1, and 15% risk of malignancy based on the presence of 0, 1 or 2 "high risk features" (cyst size >3 cm, dilated main pancreatic duct and mural nodule), with patients aft er 5 years surveillance being eight times more likely to die from causes other than from pancreatic cancer arising from their cyst. Th is concept of using the presence or absence of WF/HRS to make long-term decisions about surveillance is then further supported by several recent large studies of patients with presumed BD-IPMNs without WF surveyed for long period of time (up to 7 years), in which the 5 year disease specifi c survival is between 96-98% compared with a 28-60% risk of IPMN-related death in patient with HRS (22)(23)(24). Even in groups of elderly patients with WF, the 5-year disease specifi c survival is reported at 96% ( ref.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Additionally, there have been some retrospective studies of PC concomitant with IPMN (Table 2). 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 These studies demonstrated that the frequency of PC concomitant with IPMN ranged from 1.1% to 11.2%. As for branch duct IPMN, two working groups of JPS reported that seven PC cases were detected in 349 branch duct IPMN cases during the follow‐up period,17 and that PC concomitant with IPMN may be diagnosed earlier than ordinary PC 18.…”
Section: Risk Factors and Early Diagnosismentioning
confidence: 83%
“…Th ey then followed the patients for the long term through the Kaiser Permanente system noting the risk of pancreatic cancer and all-cause mortality. Importantly, this study cohort was assembled from 2005 extending to 2015, during which time recommendations and consensus mortality for Whipple resection is 0-2% ( 14-16 ), yet results from a study using the National Inpatient Sample of >100,000 patients reported a mortality of 4.8% ( 17 ) and other recent studies note rates of 4-8% (18)(19)(20). Finally, patient wishes must be incorporated.…”
mentioning
confidence: 99%